Nervus Olfaktorius: Dasar, Klinis Medis, dan Psikologis - Ruru, Pingkan M.; Pasiak, Taufiq F.; Kaseke, Martha M. (Universitas Sam Ratulangi, 2021)
Abstract: The olfactory nerve is the first cranial nerve. Olfactory disorders can have a negative impact on health and quality of life and affect human psychology. The aim of this study is to determine the basic anatomical, clinical medical and psychological picture of the olfactory nerve. This study was in the form of a literature review. Literature is taken from one database, namely PubMed. The keywords used were olfactory nerve anatomy AND clinical AND psychology. After being selected with inclusion and exclusion criteria, 11 literature will be reviewed. Research from 11 literature reviewed found the basic anatomy of the olfactory nerve. Clinical disorders such as anosmia, hyposmia, phantosmia can occur in several non-neurodegenerative and neurodegenerative events or diseases, namely head injury trauma, Alzheimer's, Parkinson's and COVID-19. Psychological issues related to emotional and psychiatric disorders are also related to smell. In conclusion, the first cranial nerve is the olfactory nerve or the olfactory nerve, which clinically can occur in neurogenerative and non-neurodegenerative diseases. Smell and its disturbances can have a psychological impact.Keywords: olfactory nerve, anatomy, clinical, psychology.Â Â Abstrak: Nervus olfaktorius merupakan saraf kranial pertama. Gangguan olfaktorius dapat berdampak buruk pada kesehatan dan kualitas hidup serta memengaruhi psikologis manusia. Tujuan penelitian untuk mengetahui gambaran dasar anatomi, klinis medis dan psikologis dari nervus olfaktorius. Penelitian ini dalam bentuk literature review. Literatur diambil dariÂ satu database yaitu PubMed. Kata kunci yang digunakan yaitu olfactory nerve anatomy AND clinical AND psychology. Setelah diseleksi dengan kriteria inklusi dan eksklusi didapatkan 11 literatur yang akan di review. Hasil penelitian dari 11 literatur yang di review didapatkan anatomi dasar nervus olfaktorius. Gangguan klinis seperti anosmia, hiposmia, phantosmia dapat terjadi pada beberapa kejadian atau penyakit non-neurodegeneratif dan neurodegeneratif yaitu Trauma cedera kepala, Alzheimer, Parkinson dan COVID-19. Psikologis yang berkaitan dengan emosional dan gangguan psikiatri juga berhubungan dengan penciuman. Sebagai simpulan, saraf kranial pertama adalah nervus olfaktorius atau disebut saraf penciuman, secara klinis bisa terjadi pada penyakit neurogeneratif dan non-neurodegeneratif. Penciuman dan gangguannya dapat memengaruhi psikologis.Kata kunci: Saraf olfaktori, anatomi, klinis, psikologi.